Spectral Intrinsic Decomposition Method for Adaptive Signal Representation. (13th December 2012) - Niang, Oumar; Thioune, Abdoulaye; Deléchelle, Éric; Lemoine, Jacques
Abstract : We propose a new method called spectral intrinsic decomposition (SID) for the representation of nonlinear signals. This approach is based on the spectral decomposition of partial differential equation- (PDE-) based operators which interpolate the characteristic points of a signal. The SID's components which are the eigenvectors of these PDE interpolation operators underlie the new signal decomposition-reconstruction method. The usefulness and the efficiency of this method is illustrated, in signal reconstruction or denoising aim, in some examples using artificial and pathological signals.